Molecular Typing in Bacterial Infections - de Filippis, Ivano; McKee, Marian L. (Infectious Disease, 2013)
The accurate identification and typing of microbes is essential for researchers in all fields of microbiology. The investigation of species diversity is crucial for the determination of the genetic relatedness of isolates for epidemiological studies. The development of molecular genotyping methods has improved the classification and typing of microorganisms at the sub-species level. In Molecular Typing in Bacterial Infections, readers will find an ultimate guide to molecular methods for the classification and typing of most human bacterial pathogens, covering a wide range of techniques which can be easily applied to the investigation of infectious diseases. The emphasis is on nucleic acid-based assays and alternative biochemically and immunologically-based formats providing significant potential improvement  of typing technologies that are transforming the field of diagnostic testing. Comprehensive and practical, Molecular Typing in Bacterial Infections provides state-of-the-art methods not only for accurate diagnostic, but also for the correct classification of different types which will prove to be critical in unraveling the routes of spread of human pathogens.